2002
DOI: 10.1177/0310057x0203000106
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index in Assessment of Adequacy of General Anaesthesia for Lower Segment Caesarean Section

Abstract: Awareness among parturients during general anaesthesia for caesarean section, though now uncommon, remains a concern for obstetric anaesthetists. We examined the adequacy of our general anaesthetic technique for avoiding explicit awareness by determining the depth of anaesthesia using Bispectral Index (BIS) monitoring. Twenty ASA 1 parturients having general anaesthesia for lower segment caesarean section were studied. The drugs and doses used for each anaesthetic were similar. Intraoperative Bispectral Index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Cesarean delivery under general anesthesia carries a high risk for awareness, which can be associated with hyperdynamic cardiovascular responses. 18 Studies have shown that use of BIS monitoring to guide general anesthesia, reduces awareness and recovery times. 19 remifentanil has been shown to blunt increases in BIS after tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean delivery under general anesthesia carries a high risk for awareness, which can be associated with hyperdynamic cardiovascular responses. 18 Studies have shown that use of BIS monitoring to guide general anesthesia, reduces awareness and recovery times. 19 remifentanil has been shown to blunt increases in BIS after tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a reduction in the incidence of maternal awareness from 1.3 to 0.4% following the substitution of 1% isoflurane for 0.5% halothane in their practice. Yeo & Lo [1] provided additional evidence for inadequate depth as a cause of maternal awareness when they showed that isoflurane at an endtidal concentration of 0.5-0.6% did not reliably produce BIS values < 60 in Caesarean section. We subsequently confirmed this to be true also for sevoflurane at the MAC-equivalent endtidal concentration of 1% [2].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of awareness related to obstetric anesthesia ranges from 0.4-1.3% [29,35,36]. Factors associated with obstetric anesthesia are rapid sequence induction and a reduced inhaled fraction of inhalant anesthetics [37]. Other risk factors for anesthesia awareness include the use of intravenous anesthesia as opposed to inhalant anesthetics and the premature lightening of anesthesia at the end of surgery to facilitate surgical turnover.…”
Section: Risk Factormentioning
confidence: 99%